Utilization of the Potential of Krandegan Village, Paninggaran, through the KKN of UIN Gus Dur Pekalongan Students: Pendayagunaan Potensi Desa Krandegan, Paninggaran, melalui KKN Mahasiswa UIN Gus Dur Pekalongan - Maulida Salsabila, Zita; Khoerul Mutakin, Muhamad; Fatimatuzzahro, Fatimatuzzahro; Hilman Zabidi, Arif; Safiani, Indri; Dimyathi Amin, Ahmad; Amalia Rahmah, Novita; Darmawan, Haris; Syekhira, Nabila; M. Munip, M. Munip; Nur Anisah, Dyah; Eka Sulistiya, Aryani (Dharmahita: Journal of Community Service and Development, 2024)
Field Study and Community Service (KKN) are extracurricular activities that integrate the core aspects of higher education: teaching, research, and community service. The KKN 58 Group 16 from UIN K.H. Abdurrahman Wahid Pekalongan conducted a 45-day community service program in Krandegan Village with the aim of leveraging local potential to achieve sustainable development. The group employed a combination of explanations, discussions, and direct practice methods to engage with the community. The program proceeded smoothly, largely due to the collaborative efforts of group members and the supportive village environment. The active enthusiasm of the local community further facilitated the implementation of various activities and work programs. The successful execution of these programs not only provided tangible benefits to Krandegan Village but also offered valuable learning experiences for the students, including the importance of effective communication, teamwork, and community engagement. These insights are expected to enhance future KKN activities and contribute to community development efforts.